Bahasa Inggris - Nadya Afidati; Fristika Maulida Aminatuz Zuhria; Fira Septiana; Muhid (AL QUDS : Jurnal Studi Alquran dan Hadis, 2026)
This study investigates the intellectual influence of Ahmad Hasan on Abdul Qadir Hasan in the field of hadith studies within the Islamic Union (PERSIS). The research argues that their relationship extends beyond familial ties of father and son, as it also embodies both the continuity and transformation of intellectual thought within Indonesia’s modern Islamic scholarship. Based on this assumption, the fundamental question that urgently needs to be answered is: how has the intellectual shift within the PERSIS hadith scholarly tradition unfolded as a result of intergenerational influences?  Using a literature-based and historical-intellectual approach, this study finds that Ahmad Hasan emphasized rationality, authenticity of transmission (sanad), and the rejection of weak hadith (ḍa‘īf) as part of his effort to purify Islamic teachings. Meanwhile, Abdul Qadir Hasan institutionalized these ideas through the PERSIS Hisbah Council and Islamic boarding schools, integrating contextual and social dimensions into the application of hadith. This methodological shift reflects a movement from a rational-scriptural to a rational-empirical approach that considers the objectives of Sharia (maqāṣid al-syarī‘ah) and the welfare of the community. The findings reveal that hadith thought within PERSIS has evolved epistemologically by balancing textual authenticity and social relevance. This study is expected to make an academic contribution to the development of contemporary hadith studies in Indonesia, particularly regarding the transformation of hadith methodology within modern Islamic organizations.